Changes in brain Glx in depressed bipolar patients treated with lamotrigine: a proton MRS study - Godlewska, B; Emir, U; Masaki, C; Bargiotas, T; Cowen, P (Elsevier, 2018)
Background Lamotrigine is a useful treatment in bipolar depression but requires several weeks of dose titration before its clinical effects can be assessed. Animal experimental studies suggest that lamotrigine lowers glutamate release. The aim of the current study was to assess the effect of lamotrigine on brain glutamate in depressed bipolar patients and to determine whether baseline glutamate could be used to predict clinical response. Methods We studied 21 bipolar patients who received lamotrigine treatment for a current episode of depression. Before starting lamotrigine and after 10–12 weeks treatment, patients underwent proton magnetic resonance spectroscopy (MRS) scanning at 3 Tesla where levels of glutamate (measured as Glx) were determined in anterior cingulate cortex (ACC). Results Overall, lamotrigine treatment had no significant effect on Glx levels in ACC. However, in patients who responded clinically to lamotrigine treatment Glx concentrations were significantly increased. Baseline levels of Glx did not predict response to lamotrigine. Limitations The main limitation of the study was the modest sample size. Most patients were medicated which may have modified the effect of lamotrigine on glutamate activity. MRS at 3T cannot give a reliable estimate of glutamate separate from its main metabolite, glutamine, and thus changes in Glx may not give a precise estimate of effects of lamotrigine on glutamate itself. Conclusion Lamotrigine does not appear to have a direct effect on glutamate levels in ACC in bipolar patients. However, therapeutic improvement during lamotrigine was associated with increased Glx, suggesting that alterations in glutamatergic activity might be related to recovery from bipolar depression.